Enhancing Arabic Speaking Skills Through Habit Formation in Bilingual Education - Fitriyah, Khoirunnisa'il; Wargadinta, Wildana; Taufiqurrohman, H.R.; Adam Ibrohim, Faishol Mahmud (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2024)
Developing effective Arabic speaking skills is essential in bilingual education, particularly for fostering fluency and confidence among students. This study aimed to address the gap in understanding how habit formation enhanced Arabic speaking proficiency. The objectives were: (1) to analyze the process of habit formation and its impact on students' speaking skills, (2) to evaluate proficiency levels achieved through habitual practices, and (3) to examine challenges students experienced in Arabic speaking and how these were addressed through targeted activities. Using a qualitative descriptive method, data were collected through interviews, participant observation, and document analysis. Semi-structured interviews with students, teachers, and administrators provided insights into habit formation, while observations in classroom activities allowed real-time assessment of speaking habits. Document analysis of school policies and progress reports offered a comprehensive view of strategies used to enhance Arabic speaking skills. The findings indicated that speaking habits were influenced by student motivation and bilingual policies, with routines and discipline monitoring in place. Most students demonstrated fluency, good vocabulary, and intonation, though some required improvement. Challenges such as fear of speaking and limited vocabulary were mitigated through activities like expression theater, lectures, and communicative methods. This article highlighted the importance of structured habit formation in improving Arabic speaking skills and suggested that prioritizing motivation and creative approaches could effectively help students overcome speaking challenges.